Exploring The Drivers of Earnings Management In Non-Cyclical Consumer Firms - Sarmento Giam, Howard; Pratiwi, Devica (Dinasti Publisher, 2025)
The study examines the influence of sales growth, profitability, leverage, external auditor quality, and institutional ownership on earnings management in non-cyclical consumer firms listed on the Indonesia Stock Exchange from 2019 to 2023. Using purposive sampling, 21 companies were selected, resulting in 105 observations analyzed through multiple regression. The results reveal that leverage significantly and negatively affects earnings management, highlighting that companies with higher leverage tend to practice less earnings management due to stricter creditor oversight. Conversely, sales growth, profitability, external auditor quality, and institutional ownership have no significant effect, suggesting these variables are not primary drivers of earnings management within this context. This research underscores the importance of effective financial management and external monitoring in mitigating earnings manipulation practices.